Biodegradation of Sodium Dodecyl Sulphate by a Locally Isolated Bacterium, Klebsiella Oxytoca Dr.Y14 - Wan Husin, Wan Surini (2006)
This study was conducted on sodium dodecyl sulphate (SDS) biodegradation. Bacteria capable of utilizing SDS as a sole source of carbon were isolated from water samples exposed with surfactants. Enrichment culture yielded several isolates capable of metabolizing SDS. Of these, Isolate S11 was selected for further studies based on its biodegradative capability as determined using methylene blue active substance (MBAS) assay. The isolate was identified as Klebsiella sp. using BiologTM identification system and was confirmed using 16S rRNA molecular phylogenetic analysis. Isolate S11 exhibited optimum growth at 37 °C in media containing high SDS concentrations (up to 1.0 g/L SDS), and is able to degrade 99% of 1.0 g/L SDS in 3 days. It requires minimal nitrogen source as low as 0.5 mg/L ammonium sulphate for optimum growth consistent with the Klebsiella genus ability to fix atmospheric nitrogen. Partially purified alkylsulphatase from S11 showed optimum enzyme activity at 80°C and at pH 8 using Tris-HCl buffer when tested using MBAS assay. The apparent Km and apparent Vmax of the SDS-degrading enzyme were determined to be 0.232 mM and 1.391 μmol per minute per mg protein respectively. The enzyme was found to be stable at room temperature for 50 days in Tris-HCl buffer at pH 7.5.